2009
DOI: 10.1097/mao.0b013e31818edf4a
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Non-Echo-Planar Diffusion-Weighted Magnetic Resonance Imaging Changes After Cholesteatoma Surgery

Abstract: TSE DW MRI holds great promise in screening for cholesteatoma as an alternative to exploratory second-look surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
116
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 18 publications
11
116
0
5
Order By: Relevance
“…Delayed postcontrast T1 spin-echo sequences improve the diagnosis of recurrent cholesteatoma and allow differentiation between scar tissue, which shows delayed enhancement, and cholesteatoma, which does not show delayed enhancement; conversely, inflammatory tissue displays early enhancement (7). However, these sequences do not provide the diagnostic performance necessary to eliminate the need for second-look surgery (7)(8)(9)(10)(11). Growing data suggest that DWI, particularly Half-Fourier acquisition single-shot turbo spin-echo (HASTE) DWI, yields better diagnostic performance for the detection of cholesteatomas (8,11).…”
mentioning
confidence: 99%
“…Delayed postcontrast T1 spin-echo sequences improve the diagnosis of recurrent cholesteatoma and allow differentiation between scar tissue, which shows delayed enhancement, and cholesteatoma, which does not show delayed enhancement; conversely, inflammatory tissue displays early enhancement (7). However, these sequences do not provide the diagnostic performance necessary to eliminate the need for second-look surgery (7)(8)(9)(10)(11). Growing data suggest that DWI, particularly Half-Fourier acquisition single-shot turbo spin-echo (HASTE) DWI, yields better diagnostic performance for the detection of cholesteatomas (8,11).…”
mentioning
confidence: 99%
“…In T1 and T2 weighted MR imaging, cerebrospinal fluid and arachnoid cyst have similar views with the cholesteatoma. However, the fluid attenuated inversion recovery (FLAIR) and on diffusion-weighted images occurs as hyperintense [10] (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these approaches to PA may not be possible when there is poor pneumatization of the temporal bone [10].…”
Section: Discussionmentioning
confidence: 99%
“…5 In another paper, the same group concluded that '[turbo spin-echo] ([halfFourier acquired single-shot turbo spin-echo]) [diffusionweighted] MRI is emerging as a cost effective, noninvasive alternative to second-look surgery for detection and screening for cholesteatoma in pediatric patients'. 6 In their study of a paediatric cholesteatoma series, the group led by Plouin-Gaudon (Centre Hospitalier de Valence) and Bossard (Hôpital Privé Jean Mermoz, Lyon, France) reported that '[half-Fourier acquired single-shot turbo spin-echo] diffusion-weighted MRI revealed a cholesteatoma in all true-positive cases.…”
mentioning
confidence: 99%
“…Dhepnorrarat et al, 5 in Australia, examined the halfFourier acquired single-shot turbo spin-echo sequence, assessing post-operative changes (and not the size of cholesteatoma detected) in MR images compared with 'second-look' surgery. Their work found encouraging results for this sequence in detecting cholesteatoma within post-operative ears.…”
mentioning
confidence: 99%